The Rise and Fall of Early American Magazine Culture - Gardner, Jared (Book collections on Project MUSE., 2012)
"Between the newly canonized novels of the 1790s and the long-familiar novels of the 1820s, early American literary magazines figured themselves as museums, bringing together a multitude of notable content and enabling readers to choose what to consume. A transatlantic literary form that refused to break with British cultural models and genealogy, the early American magazine had at its center the anonymous authority of the editor and a porous distinction between reader and author. Esteemed subscribers were treated as magnets to attract other subscribers, and subscribers were prompted to become contributors, giving these early American publications the appearance of public forums. The Rise and Fall of Early American Magazine Culture reexamines these publications and their reach to show how magazine culture was multi-vocal, as opposed to novel culture, which imposed a one-sided authorial voice and restricted the agency of the reader. In this first book-length study of the history of American magazine culture in the colonial and early national period, Jared Gardner describes how those who invested considerable energies in this form--including some of the period's most important political and literary figures such as Charles Brockden Brown and Washington Irving--sought to establish a very different model of literary culture than what came to define American literary history and its scholarship. He cautions against privileging novels or authors as the essential touchstones of American literary history and instead encourages an understanding of how the "editorial function" favored by magazine culture shaped reading and writing practices. Countering assumptions about early American print culture and challenging our scholarly fixation on the novel, Gardner reimagines the early American magazine as a rich literary culture that operated as a model for nation-building by celebrating editorship over authorship and serving as a virtual salon in which citizens were invited to share their different perspectives. This important work revisits largely lost interventions in the forms and politics of literature and sounds a vibrant call to radically revise early American literary history."--Jacket